Are PEEK‐on‐Ceramic Bearings an Option for Total Disc Arthroplasty? An In Vitro Tribology Study. Issue 11 (November 2016) - Siskey, Ryan; Ciccarelli, Lauren; Lui, Melissa K. C.; Kurtz, Steven M.
Abstract: Background: Most contemporary total disc replacements (TDRs) use conventional orthopaedic bearing couples such as ultrahigh‐molecular‐weight polyethylene (polyethylene) and cobalt‐chromium (CoCr). Cervical total disc replacements incorporating polyetheretherketone (PEEK) bearings (specifically PEEK‐on‐PEEK bearings) have been previously investigated, but little is known about PEEK‐on‐ceramic bearings for TDR. Questions/purposes: (1) What is the tribologic behavior of a PEEK‐on‐ceramic bearing for cervical TDR under idealized, clean wear test conditions? (2) How does the PEEK‐on‐ceramic design perform under impingement conditions? (3) How is the PEEK‐on‐ceramic bearing affected by abrasive wear? (4) Is the particle morphology from PEEK‐on‐ceramic bearings for TDRs affected by adverse wear scenarios? Methods: PEEK‐on‐ceramic cervical TDR bearings were subjected to a 10 million cycle ideal wear test based on ASTM F2423 and ISO 181912‐1 using a six‐station spine wear simulator (MTS, Eden Prairie, MN, USA) with 5 g/L bovine serum concentration at 23° ± 2° C (ambient temperature). Validated 1 million cycle impingement and 5 million cycle abrasive tests were conducted on the PEEK‐on‐ceramic bearings based, in part, on retrieval analysis of a comparable bearing design as well as finite element analyses. The ceramic‐on‐PEEK couple was characterized for damage modes, mass and volume loss, and penetration and the lubricant was subjected to particle analysis. The resulting mass wear rate, volumetric wear rate, based on material density, and particle analysis were compared with clinically available cervical disc bearing couples. Results: The three modes of wear (idealized, impingement, and abrasive) resulted in mean mass wear rates of 0.9 ± 0.2 mg/MC, 1.9 ± 0.5 mg/MC, and 2.8 ± 0.6 mg/MC, respectively. The mass wear rates were converted to volumetric wear rates using density and found to be 0.7 ± 0.1 mm 3 /MC, 1.5 ± 0.4 mm 3 /MC, and 2.1 ± 0.5 mm 3 /MC, respectively. During each test, the PEEK endplates were the primary sources of wear and demonstrated an abrasive wear mechanism. Under idealized and impingement conditions, the ceramic core also demonstrated slight polishing of the articulating surface but the change in mass was unmeasurable. During abrasive testing, the titanium transfer on the core was shown to polish over 5 MC of testing. In all cases and consistent with previous studies of other PEEK bearing couples, the particle size was primarily < 2 μm and morphology was smooth and spheroidal. Conclusions: Overall, the idealized PEEK‐on‐ceramic wear rate (0.7 ± 0.1 mm 3 /MC) appears comparable to the published wear rates for other polymer‐on‐hard bearing couples (0.3‐6.7 mm 3 /MC) and within the range of 0.2 to 1.9 mm 3 /MC reported for PEEK‐on‐PEEK cervical disc designs. The particles, based on size and morphology, also suggest the wear mechanism is comparable between the PEEK‐on‐ceramic couple and other polymer‐on‐ceramic orthopaedic couples. Clinical Relevance: The PEEK‐on‐ceramic bearing considered in this study is a novel bearing couple for use in total disc arthroplasty devices and will require clinical evaluation to fully assess the bearing couple and total disc design. However, the wear rates under idealized and adverse conditions, and particle size and morphology, suggest that PEEK‐on‐ceramic bearings may be a reasonable alternative to polyethylene‐on‐CoCr and metal‐on‐metal bearings currently used in cervical TDRs.